2008
DOI: 10.1016/j.vaccine.2008.05.018
|View full text |Cite
|
Sign up to set email alerts
|

CD40L expressed from the canarypox vector, ALVAC, can boost immunogenicity of HIV-1 canarypox vaccine in mice and enhance the in vitro expansion of viral specific CD8+ T cell memory responses from HIV-1-infected and HIV-1-uninfected individuals

Abstract: SummaryHuman immunodeficiency virus-1 (HIV-1) canarypox vaccines are safe but poorly immunogenic. CD40 ligand (CD40L), a member of the tumor necrosis factor superfamily (TNFSF), is a pivotal co-stimulatory molecule for immune responses. To explore whether CD40L can be used as an adjuvant for HIV-1 canarypox vaccine, we constructed recombinant canarypox viruses expressing CD40L. Co-immunization of mice with CD40L expressing canarypox and the canarypox vaccine expressing HIV-1 proteins, vCP1452, augmented HIV-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 62 publications
(83 reference statements)
2
31
0
Order By: Relevance
“…It is believed that the adjuvant effect is mediated at least in part through enhanced antigen presentation by specific B cells [373]. Such immune enhancement activity of CD40 antibody is similar to that of CD40 ligand, which has been shown to enhance cellular immune activity in mice [374]. Conjugation of anti-CD-40 to antigen (HSV glycoprotein D) enhanced the immunogenicity of the antigen [375].…”
Section: Specific Peptides/proteinsmentioning
confidence: 99%
“…It is believed that the adjuvant effect is mediated at least in part through enhanced antigen presentation by specific B cells [373]. Such immune enhancement activity of CD40 antibody is similar to that of CD40 ligand, which has been shown to enhance cellular immune activity in mice [374]. Conjugation of anti-CD-40 to antigen (HSV glycoprotein D) enhanced the immunogenicity of the antigen [375].…”
Section: Specific Peptides/proteinsmentioning
confidence: 99%
“…Considerable research has been conducted using DNA vaccines (individually or with proteins and/or cytokines), 25 Ad-based vaccines (replication competent or replication deficient), vaccinia virus-based vaccines (MVA, canarypox virus (ALVAC) and attenuated vaccinia (NYVAC)), [31][32][33][34][35][36] and other vectors 37,38 alone or in combination to induce antigen-specific anti-retroviral responses in animals. Administration of a recombinant viral vector can induce strong humoral and cellmediated immune responses against both transgene and viral vectors.…”
Section: Discussionmentioning
confidence: 99%
“…We first tested this hypothesis in mouse model. We constructed recombinant ALVAC viruses that can express various murine TNFSF molecules, including CD40L, OX40L and others 4,5 (and Liu J, et al unpublished data). For CD40L, we constructed ALVAC vectors expressing either membrane CD40L (vCPmCD40L) or soluble multimeric CD40L (vCPmSP-D-CD40L), since a previous study reported that the fusion protein of surfactant protein D (SP-D) and CD40L, SP-D-CD40L, could promote CD40L to form soluble multimer, which was superior to membrane CD40L in augmenting immunogenicity elicited by an HIV-1 DNA vaccine in mice.…”
Section: Challenges and Prospectsmentioning
confidence: 99%
“…Using mouse model, we found some TNFSF molecules could augment cellular immune responses elicited by an ALVAC HIV-1 vaccine, vCP1452. 4,5 In this commentary, we will describe our experience in using TNFSF molecules as adjuvants for vCP1452 in mice, and briefly discuss challenges and prospects of using TNFSF molecules as adjuvants for ALVAC HIV-1 vaccines in clinical trials.…”
mentioning
confidence: 99%